Qualidade de vida de profissionais que atuam na saúde mental - Andrade, Vivian Maria Sandri (2017)
The importance of investigating the quality of life (QOL) of certain groups, has been increasing as a measure of assessment of health care treatment outcomes. According to the World Health Organization (WHO), QOL is the individual's perception of his or hers position in life, in the cultural context and value system in which he lives and, in relation to his goals, expectations, standards and concerns. Therefore, the objective of this study was to investigate and compare the QOL among mental health professionals in the city of Agudos, Bauru and Jaú - SP, through the application of a questionnaire on sociodemographic attributes of a work impact scale on mental health services satisfaction – IMPACTO-BR Abbreviated Form and QOL through WHOQOL-Bref of the WHO. The results demonstrated that the level of the workers' global overload was between 1.5 and 2.2. The highest values of overload were observed in the Agudos group. Regarding QOL, all mean scores ranged from 53.1 (AGUDOS Self Assessment) to 74.5 (JAÚ Social Relations). According to the results obtained, low rates of work overload and high QOL percentages were identified for the mental health professionals of the 3 groups studied, with the Agudos group being a negative one